(untitled) (Research, Society and Development, 2024)
The aim of this review is to understand how the nursing team can make a difference in the care of children with epidermolysis bullosa (EB) and their families. This study seeks to evaluate the effectiveness of nurses in providing direct care, including wound management, pain control, and health promotion. Additionally, it aims to explore the importance of emotional support, identifying how the psychological support offered by nurses can help families cope with the stress and anxiety associated with the condition. Another important aspect is to identify the need for specific training for nurses, discussing the relevance of training that enables professionals to provide appropriate and comprehensive guidance. We conducted a literature review in databases such as PubMed, SciELO, and BVS, focusing on publications from 2019 to 2024 that address nursing care, psychological impact, and pain management in children with EB. After careful analysis, we selected 10 relevant studies from 131 articles. This analysis revealed that the guidance and support provided by nurses have a profound impact on the quality of life of children and their families. Proper care and effective pain management strategies not only reduced complications but also aided in wound healing. Psychological support was essential for caregivers, fostering a more welcoming family environment. The role of the nursing team is crucial for the physical health of children and the emotional well-being of their families. Investing in continuous training is vital for providing more effective and humane care.